Pengaruh Kubebin, Senyawa Lignan Pqner cubeba L.f. terhadap Pelepasan Histamin dari RPMCs - AGUNG ENDRO NUGROHO; WAHYONO WAHYONO; SUBAGUS WAHYUONO; KAZUTAKA MAEYAMA (JURNAL ILMU KEFARMASIAN INDONESIA, 2010)
Cubebin is a lignan isolated from Indonesian plant Piper cubeba L.f fruits. Cubebin has been found to strongly inhibit contraction of isolated-trachea of guinea pig induced by histamine or metacholine. ln the present study, the effcct of cubebin was investigated on histamine release from rat peritoneal mast cells (RPMCS), a connective tissue mast cell. Compound 48/80 (G Protein activator), thapsigargin (SERCA inhibitor), ionoinycin (calcium ionophore), and PMA (PKC activator) were used as inducers for histamine release from connective tissue mast cell. Histamine released in the medium was measured by HPLC-Huorometry. The results showed that cubebin at the concentration of 30 and 100 µM inhibited the histamine release from RPMCS induced by thapsigargin by 12,86 ± 1,84 % and 40.38 ± 1.93 %, respectively. In addition, there was a partial inhibition seen in respond to ionornycin, with no effects towards compound 48/80 or PMA, These data indicate that cubebin inhibited thc histamine release from connective mast cells, and might involve in the activation of sarco/ endoplasmic reticulum Ca2+ ATPase.